A 24-h helpline for access to expert management advice for food allergy-related anaphylaxis in children: protocol for a pragmatic randomised controlled trial. Issue 4 (13th August 2012) - Kelleher, Maeve M; Hourihane, Jonathan O'B; DunnGalvin, Audrey; Cullinane, Claire; Fitzsimons, John; Sheikh, Aziz
Abstract : Objectives: Anaphylaxis is an important, potentially life-threatening paediatric emergency. It is responsible for considerable morbidity and, in some cases, death. Poor outcomes may be associated with an inability to differentiate between milder and potentially more severe reactions and an associated reluctance to administer self-injectable adrenaline. This study aims to assess the effectiveness of a 24-h telephone access to specialist paediatric allergy expert advice in improving the quality of life of children and their families with potentially life-threatening food allergy (ie, anaphylaxis) compared with usual clinical care. Methods and analysis: Children aged less than 16 years with food allergy and who carry an adrenaline autoinjector will be recruited from the Paediatric Allergy Clinic at Cork University Hospital, Ireland and baseline disease-specific quality of life will be ascertained using the validated Food Allergy Quality of Life Questionnaire (FAQLQ). Participants will be randomised for a period of 6 months to the 24-h telephone specialist support line or usual care. The primary outcome measure of interest is a change in FAQLQ scores, which will be assessed at 0, 1 and 6 months postrandomisation. Analysis will be on an intention-to-treat basis using a 2×3 repeated measures within-between analysis of variance. Although lacking power, we will in addition assess the impact of the intervention on a range of relevant process and clinical endpoints. Ethics and dissemination: This trial protocol has been approved by the Clinical Research Ethics Committee of the Cork Teaching Hospitals. The findings will be presented at international scientific conferences and will be reported on in the peer-reviewed literature in early 2013.